Author Correction: 4-dimensional functional profiling in the convulsant-treated larval zebrafish brain. Issue 1 (December 2018) - Winter, Matthew; Windell, Dylan; Metz, Jeremy; Matthews, Peter; Pinion, Joe; Brown, Jonathan; Hetheridge, Malcolm; Ball, Jonathan; Owen, Stewart; Redfern, Will; Moger, Julian; Randall, Andrew; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.